2002
DOI: 10.1055/s-2002-32000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endoscopic Hemostasis in Upper Gastrointestinal Bleeding Related to Mallory-Weiss Syndrome

Abstract: Our results suggested that endoscopic hemostasis is not necessary in patients without active bleeding stigmata, and the mechanical hemostatic method is more effective than HSE injection in patients with active bleeding stigmata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 7 publications
0
39
0
2
Order By: Relevance
“…However, when bleeding is active and severe, patients require surgical treatment or nonsurgical therapeutic approaches [4,5] . Several endoscopic methods have been used to treat actively bleeding MWS, including injection of different agents, electrocoagulation, application of hemoclips, and band ligation [8,18] . Thermal coagulation or injection therapies have been used successfully to control active bleeding from MWS [10][11][12]21] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when bleeding is active and severe, patients require surgical treatment or nonsurgical therapeutic approaches [4,5] . Several endoscopic methods have been used to treat actively bleeding MWS, including injection of different agents, electrocoagulation, application of hemoclips, and band ligation [8,18] . Thermal coagulation or injection therapies have been used successfully to control active bleeding from MWS [10][11][12]21] .…”
Section: Discussionmentioning
confidence: 99%
“…EBL is technically easier to perform than other methods, with the lesions well viewed under direct pressure and suction from the transparent ligation cap [20] . The use of EBL for treatment of patients with bleeding MWS has been described in several studies [13][14][15]18,20,24] . Our study also demonstrated high successful rates of primary and permanent hemostasis in such cases.…”
Section: Peer Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients with MWS, the reported rates of primary hemostasis obtained with epinephrine injection range from 93% to 100%. However, bleeding recurs in 5.8% to 44% of patients with actively bleeding MWS (10,11). Furthermore, in thermal endoscopic therapy, endoscopists have to be careful to manage the relatively thin esophageal wall and few fibrotic bases in patients with MWS.…”
Section: Discussionmentioning
confidence: 99%